Early Theological Disputes: History and Main Thoughts of the Jabariyyah and Qadariyyah - Miftahul Jannah; Indo Santalia (ALSYS, 2026)
This study examines the historical emergence and core doctrines of the Jabariyyah and Qadariyyah sects, two pivotal extremist schools in early Islamic theology that polarized debates on divine predestination (qadha’ and qadar) and human free will (ikhtiar) during the Umayyad era. Employing a qualitative library research design, it synthesizes classical heresiographical texts and modern analyses through descriptive–analytical and hermeneutic approaches to reconstruct their socio-political origins, doctrinal tenets, and theological implications. The findings show that Jabariyyah thought, rooted in pre-Islamic fatalism and crystallized in khālisah (extreme) and mutawassiṭah (moderate) strands associated with Jahm ibn Ṣafwān, conceptualizes humans as majbūr (compelled) agents whose acts are created directly by Allah, thereby negating moral responsibility while affirming taʿṭīl (denial of divine attributes), khalq al-Qur’ān (the created Qur’an), and the rejection of afterlife vision (ru’yah). Conversely, Qadariyyah, pioneered by Maʿbad al-Juhanī and Ghailān al-Dimashqī, advances an absolutist view of human autonomy that rejects divine decree, static faith (īmān), and essential attributes, yet converges paradoxically with Jabariyyah on the created status of the Qur’an. These antithetical positions—Jabariyyah determinism undermining tawḥīd rubūbiyyah and Qadariyyah humanism eroding divine omniscience—arose within an Umayyad political context that instrumentalized doctrine, catalyzing the development of ‘ilm al-kalām and the articulation of an Ahlus Sunnah via media position centered on kasb (act acquisition). The analysis underscores their deviation from Salaf orthodoxy, supported by mutawatir Qur’anic and hadith evidence (e.g., QS. An-Nisa’: 57; Ṣaḥīḥ Muslim on ru’yah), and highlights their continuing relevance for contemporary ethical debates on agency and accountability in a globalized context. Limited by its reliance on textual sources, this study contributes to Islamic intellectual historiography by clarifying the theological roots of extremism and advocating doctrinal moderation with implications for interfaith and philosophical dialogue.